Single-mode D-shaped optical fiber sensor for the refractive index monitoring of liquid - Qazi, H. H. (Taylor and Francis Ltd., 2016)
A new fabrication method is introduced for the production of D-shaped optical fiber. A mechanical end and edge polishing system with aluminum oxide polishing film is utilized to perform sequential polishing on one side (lengthwise) of single-mode optical fiber in order to obtain a D-shaped cross section. Adjusting specific mechanical parameters allows for control of the volume of the D-shaped zone, while the fiber surface smoothness is governed by selection of polishing film grit size. To meet the accuracy and repeatability requirements, optical power loss is monitored during the entire polishing process in situ and in real time. This proposed technique possesses advantages of rapidity, safety, simplicity, repeatability and stability with high precision in comparison with contemporary methods for production. Sensor performance tests on the fiber reveal a linear response with linearity up to R2 = 0.984 for surrounding refractive index in the range of 1.320-1.342 refractive index, which corresponds to different concentrations of the glucose solution test environment. The produced D-shaped optical fiber has potential sensing and monitoring applications in chemical, environmental, biological and biochemical fields.